(untitled) (Comprehensive Journal of Science, 2025)
This study aims to examine the role of Information Technology Governance (ITG) in enhancing the quality of internal auditing in commercial banks operating in the city of Zawiya, in light of the increasing expansion in the use of information systems and the accompanying technological risks and regulatory challenges. The study is based on a central problem concerning the extent to which IT governance practices contribute to supporting the effectiveness and quality of internal audit functions within commercial banks The study adopts a descriptive–analytical approach. Data were collected through a questionnaire distributed to a sample of 95 respondents from employees working in commercial banks, including internal audit, information technology, financial management, and other related control units. A set of appropriate descriptive and inferential statistical methods was used to analyze the data in line with the nature of the study hypotheses. The results indicate that IT governance practices are applied at a moderate level with an upward tendency, while internal auditing demonstrates a high level of quality. The findings also reveal that IT governance plays an effective role in supporting the effectiveness of internal auditing in dealing with technological risks, in addition to its contribution to enhancing the overall quality of internal audit activities. Based on these results, the study recommends strengthening IT governance frameworks, developing the technical capabilities of internal auditors, and enhancing coordination between information technology units and internal audit functions, in order to improve internal audit quality and enhance the effectiveness of internal control systems in commercial banks.